ANALYSIS COMPENSATION AND SUPERVISION OF EMPLOYEES JOB SATISFACTION AT PT. OLAM INDONESIA UNIT MEDAN - Sartika Ningsih; Ahmad Azmi; Siswa Pratama (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The purpose of this study is to gain an understanding of the benefits and disadvantages of the compensation and benefits package for employees working at the PT. Olam Indonesia Unit in Medan. The type of research being conducted here is known as associative research, which takes a quantitative approach. For the purpose of data analysis, the technique employs linear regression analysis with the SPSS version 25 statistical software. One hundred and eighty employees from the PT. Olam Indonesia Unit in Medan are the sample size for this study. In this particular research project, the method of data collection that is being utilized is known as questionnaire. The results of the research indicate that there is a positive correlation between the amount of compensation received and the amount of work performed, as well as the benefits received from the work performed. Last but not least, compensation and benefits are beneficial in relation to the performance of work.